Addressing Inequities in Biopiracy and Biodiversity Through International Legal Frameworks - Nazem, Suhaba Nizar; Jasim, Imad Obaid; Khalaf, Laith Rafea; Al-Musawi, Oudha Yousif Salman; Chornomordenko, Dmytro (Journal of Ecohumanism, 2024)
Background: Biopiracy, the illegal exploitation of biological resources, primarily from impoverished nations, has generated worldwide biodiversity and equity concerns. The Global South loses biodiversity and cultural heritage due to a lack of legal and institutional frameworks to conserve its biological resources. Objective: To assess the efficacy of international legal frameworks in resolving biopiracy imbalances and recommend better biodiversity and indigenous knowledge protection solutions. Methods: International accords like the CBD and Nagoya Protocol and biopiracy case studies were reviewed for a complete analysis. This qualitative technique revealed the legal system's strengths and flaws. Results: International legal frameworks have recognized indigenous rights and provided benefits-sharing structures, but enforcement, compliance, and fair benefit distribution remain issues. The widespread commitment to these agreements is necessary to maintain their efficacy. Conclusion: Stronger international legal frameworks with robust enforcement mechanisms and worldwide collaboration are needed to prevent biopiracy and maintain biodiversity. These frameworks must also recognize and incorporate indigenous knowledge and practices for fair and sustainable biological resource use.